Efficacy of Virtual Reality in Upper Limb Rehabilitation in Patients with Spinal Cord Injury: A Pilot Randomized Controlled Trial - Somya Prasad; Ruby Aikat; Satyanarayana Labani; Neha Khanna (Asian Spine Journal, 2018)
Study Design Pilot randomized controlled trial. Purpose To compare the efficacy between virtual reality intervention (using Nintendo Wii) along with conventional occupational therapy and conventional occupational therapy alone in improving upper limb function in patients with spinal cord injury (SCI). Overview of Literature The use of virtual reality has gained importance in the rehabilitation sector over the last few years. Nintendo Wii has the potential to encourage upper limb function while engaging in an interesting activity, which is important in long-term interventions, such as the treatment of SCI. Methods Overall, 22 patients with SCI participated in the study. They were randomly assigned to two groups. Group I received 30 minutes of virtual reality intervention (using Nintendo Wii) and 30 minutes of conventional therapy, whereas group II received conventional therapy only for 30 minutes. Both groups received therapy 3 days a week for 4 weeks. One hand of each patient was identified as the target hand based on the inclusion criteria. All patients were assessed at baseline, 2 weeks and 4 weeks (post-intervention), and 6 weeks (follow-up). The functional ability of the target hand was assessed using the Capabilities of Upper Extremity (CUE) questionnaire. Gross motor dexterity was assessed using the Box and Block Test (BBT). The level of independence in activities of daily living was assessed by the Spinal Cord Independence Measure-Self Report and quality of life by the World Health Organization Quality of Life-BREF. Results After 4 weeks of intervention, there was no significant difference in improved hand function between the groups. Mean scores were higher for group I than for group II, with a higher percent change (31.5% in CUE questionnaire and 51.7% in BBT) in group I. Conclusions Virtual reality along with conventional therapy produces similar results in upper limb function as does conventional therapy alone.